Storage Effects of Low Temperature on the Quality Parameters of Mince Based Fish Stick Prepared from Silver Carp (Hypophthalmichthys molitrix) - Shikha, FH; Hossain, MI; Ali, MHI (Journal of Environmental Science and Natural Resources, 2021)
It is important to preserve the fish products in proper storage condition until further use. Keeping this point in view, fish stick prepared from silver carp (Hypophthalmichthys molitrix) mince by using different kinds of food additives were stored at refrigeration (5 to 8°C) and frozen temperatures (-18 to -20°C) temperature. The results showed that, on “0” day the sensory quality criteria score was 9.00±0.00a for general appearance which decreased to 8.70±0.39a after 3 days of storage at refrigeration temperature and to 8.49±0.41aat frozen temperature after 56 days of storage. The TVBN values were found 22.54±0.17aand 16.04±0.39a, respectively at refrigeration and frozen temperatures which was 7.84±0.95c on “0” day. The peroxide value of the product on “0” day was 6.19 ± 0.71eand the microbial load was 1.49 x104 CFU/g which reached to 19.94 ± 0.17a, 21.58 ± 0.78a meq/kg and 2.13 x107 CFU/g, 1.12 ×102 CFU/g after storage at refrigeration and frozen temperatures. By observing these results present study could be concluded as-frozen temperature storage is comparatively better than refrigeration temperature for storing minced based ‘ready to cook’ products like fish stick and at this temperature the product can be stored for about 8 weeks. Environ. Sci. & Natural Resources, 12(1&2): 175-180, 2019